Hidden transcripts, moral and policy entrepreneurs, and human trafficking legislation in South Africa - Yaso, Masibulele (My University, 2015)
In 2013 South Africa signed the Prevention and Combating of Trafficking in Persons Bill into law. During the run-up to 2010 FIFA Soccer World Cup in South Africa, early drafts of this bill were almost steamrolled through parliament. The proposed anti-human trafficking bill generated huge public interest. The soccer event provided a perfect opportunity for moral and policy entrepreneurs to manufacture and stage moral panic about the problem of human trafficking in the country. These moral or policy entrepreneurs – the anti-prostitution and human trafficking organisations – employed a victimhood approach to justify the intensification of ‘urgent law enforcement’ to deal with human trafficking. The exploitation of women and children in the sex industry became a rallying point for moral and policy entrepreneurs. Hence, government awareness campaigns, during the run up to the 2010 FIFA World Cup, were characterised by desperate language such as trafficking of women and children for sexual purposes. The South African government hastily responded by announcing a proposed anti-human trafficking bill. The bill was introduced in parliament for discussion two months before the kick-off of the sporting event. This happened; despite the fact government did not provide empirical evidence showing a rise in, or alarming statistics about, human trafficking. Parliament refused to debate the bill. The decision by parliament - to put on hold the discussion and the passing of the bill - was in fact an act of legislative sovereignty. However, both the actions of government, NGOs and parliament must be understood in the context of playing out what Scott (1990) refers to as ‘dominance and the art of resistance’. The sovereign practise by legislators was a particular form of political disguise. South Africa did not want to openly rebel against the dominant agenda behind anti-human trafficking bill.
Master’s Thesis submitted to the African Centre for Migration and Society. Faculty of Humanities University of the Witwatersrand Date: 06 February 2015